2020
DOI: 10.3390/biom10030444
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Resolving Effect of Ginsenosides as an Anti-Inflammatory Mechanism of Panax ginseng

Abstract: Panax ginseng, also known as Korean ginseng, is a famous medicinal plant used for the treatment of many inflammatory diseases. Ginsenosides (ginseng saponins) are the main class of active constituents of ginseng. The anti-inflammatory effects of ginseng extracts were proven with purified ginsenosides, such as ginsenosides Rb1, Rg1, Rg3, and Rh2, as well as compound K. The negative regulation of pro-inflammatory cytokine expressions (TNF-α, IL-1β, and IL-6) and enzyme expressions (iNOS and COX-2) was found as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 76 publications
2
94
0
Order By: Relevance
“…Akao et al [ 16 ] investigated the absorption of CK in rat plasma, and Lee et al [ 17 ] demonstrated the absorption, distribution, and metabolism of CK in humans. CK is one of the rare ginsenosides, and it is of great interest due to its diverse biological activities and high pharmacological activities [ 18 , 19 ]. However, the minute amount of CK in ginseng cannot satisfy the needs of commercial purposes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akao et al [ 16 ] investigated the absorption of CK in rat plasma, and Lee et al [ 17 ] demonstrated the absorption, distribution, and metabolism of CK in humans. CK is one of the rare ginsenosides, and it is of great interest due to its diverse biological activities and high pharmacological activities [ 18 , 19 ]. However, the minute amount of CK in ginseng cannot satisfy the needs of commercial purposes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of gintonin on cell viability against iodoacetic acid (IAA)-mediated HT22 cell death. (A) IAA-induced cell death in a dose-dependent manner in HT22 cells treated with multiple concentrations of IAA (1,3,5,10,15, and 20 μM) for 2 h. (B) Dose-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis. After treating with 5 μM IAA for 2 h, HT22 cells were exposed to various concentrations of gintonin (0.1, 0.3, 1, 3, and 10 μg/mL) for 24 h. (C) Time-dependent effect of gintonin on cell viability against IAA-mediated cell apoptosis.…”
Section: Figurementioning
confidence: 99%
“…However, despite the promising results in preclinical models, the multidomain clinical trial MAPT study showed that PUFA supplementation had no significant effects on cognitive decline over three years in elderly people with memory complaints [ 91 ]. Another nutraceutical commonly used as a herbal medicine and food supplement given its anti-inflammatory properties is ginsenoside (ginseng saponin) [ 92 ]. Ginsenosides are amphipathic compounds, acting as partial agonists of steroid hormone receptors, regulating metabolism and inflammation [ 93 ].…”
Section: Nutraceuticals As a Treatment Of Admentioning
confidence: 99%